Managing Robotics in Retail - A Service Systems Perspective - Meyer, Patrick (Friedrich-Alexander-Universität Erlangen-Nürnberg, 2022)
This book answers the question of how to manage service robots in brick-and-mortar dominated retail service systems to allow for key stakeholders’ adoption and to foster value co-creation. It starts by demonstrating the scientific relevance of the topic as well as deriving a set of promising research questions. After introducing service-dominant logic as a theoretical research lens and elucidating service systems along with their underlying concept of value co-creation as relevant key concepts, five studies are presented. The author´s findings show that understanding and differentiating between consensus, shared and idiosyncratic drivers of and barriers to the adoption of service robots in retail service systems by all key stakeholders, i.e. customers, frontstage employees, and retail managers, is crucial to be able to fully cope with the complexity inherent in the adoption of service robots in service organizations. Moreover, the designed and evaluated artifact fosters a paradigm shift from a one-time technology introduction to a continuous technology management approach including iterations of experimenting, piloting, and implementing.<br
Keywords: Human-computer intercation; service systems; Retailing; Robots; Service robots; Technology adoption; human-robot interaction; artificial intelligence; service innovation